Determinación del grado de eficiencia de la planta de tratamiento de aguas residuales domésticas en la localidad de Segunda Jerusalén - Raccbumí Linares, Karem Cbristy Giuliana (2016)
The country has a lot of effluents from treatment plants or Municipal Wastewater (WWTP) that are discharged into natural water bodies, affecting their quality. As of April 1, 2009 carne into force No. 29338, Law on Water Resources Act, which states that the National Water Authority is responsible for the protection of water as a water resource. In this sense, controls, supervises and monitors compliance with water quality standards based on the National Environmental Quality Standards for Water (ECA-Water). In that sense, this project sought to determine the efficiency of the treatment plant domestic wastewater in the city of Jerusalem Second- Rioja 2014. The parameters subject to monitoring WWTP effluents were as shown in S.D. No. 003- 2010-MINAM for which the maximum permissible limits are fixed. These are: Oils and Fats, thermotolerant coliforms, biochemical oxygen demand, chemical oxygen demand, pH, total suspended solids and temperature. These parameters were monitored in the raw wastewater (influent) and treated wastewater (effiuent), taking in all cases single samples. The parameters had higher levels of efficiency in descending order were the Thermotolerant Coliform with 94.63%, total suspended solids with 86.52%, chemical oxygen demand with 76.65%, with 75.09 Oils and Fats, biological oxygen demand with 75.06%, pH 1.05% with respectto temperature with -2.89%, the negative value is a result there is a decrease between the influent and effiuent. The values of thermotolerant coliforms, COD, BOD 5 and PH, reported values obtained regardless of the degree of efficiency, the values do not meet the maximum permissible limits established in the DS N o 003-2008- MINAM situation possibly influenced by production DB05 residual due to the decomposition of waste water plants and other natural organic matter present in the lagoons. The treatment system achieving good efficiency in the removal of oils and fats, presented a value of 75.09%, indicating that according to the limits for the control of discharges S.D. No. 003-2008-MINAM complies with the requirements